Ischaemic preconditioning of skeletal muscle 2. Investigation of the potential mechanisms involved. - Bushell, A; Klenerman, L; Davies, H; Grierson, I; McArdle, A; Jackson, M (2002)
We have previously shown that prior exposure of rat hind limbs to ischaemia for five minutes and reperfusion for five minutes reduced the structural damage to skeletal muscle which followed a subsequent period of ischaemia for four hours and reperfusion for one hour. We have now examined the potential mechanisms by which this ischaemic preconditioning protocol may be effective in reducing damage to skeletal muscle induced by prolonged ischaemia and reperfusion. Prior exposure of the hindlimb to ischaemia for five minutes and reperfusion for five minutes did not prevent the fall in the ATP content of tibialis anterior which occurred after a subsequent period of ischaemia for four hours and reperfusion for one hour. Similarly, no effect of the preconditioning protocol was seen on the elevated muscle myeloperoxidase, indicative of an elevated neutrophil content, or abnormal muscle cation content. Reperfused ischaemic muscle was also found to have an increased content of heat-shock protein (HSP) 72, but the preconditioning protocol did not further increase the content of this or other HSPs indicating that it was not acting by increasing the expression of these cytoprotective proteins. The protective effects of preconditioning appeared to be mimicked by the infusion of adenosine to animals immediately before exposure to the four-hour period, indicating a potential mechanism by which skeletal muscle may be preconditioned to maintain structural viability.